2021
DOI: 10.1097/bpb.0000000000000884
|View full text |Cite
|
Sign up to set email alerts
|

Golf cart injuries in children: the experience of trauma centers in a single state in the USA

Abstract: Golf carts remain a source of morbidity in children. We aimed to establish the incidence and injury characteristics of pediatric patients injured due to golf cart usage over an 11-year period. This is a retrospective study using a single state trauma database of patients ages 0-17 years admitted to a trauma center and who sustained injures while a golf cart was in use. Thirteen Pediatric and Adult Trauma Centers within the state of Pennsylvania were evaluated from 1 January 2004 to 31 December 2014. The inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…During the last several years, there has been increasing recognition of the dangers of GC use and their potential as a cause of significant trauma among pediatric providers. [2][3][4] Our data adds to the current discourse surrounding GC, their increasing use as personal transport, and the increasing number of GC injuries as a result. The potential for injury with ATV use has long been recognized.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…During the last several years, there has been increasing recognition of the dangers of GC use and their potential as a cause of significant trauma among pediatric providers. [2][3][4] Our data adds to the current discourse surrounding GC, their increasing use as personal transport, and the increasing number of GC injuries as a result. The potential for injury with ATV use has long been recognized.…”
Section: Discussionmentioning
confidence: 71%
“…There is mounting data to suggest that the severity of GC injuries in the pediatric population is underappreciated. [1][2][3][4] To clarify the frequency and severity of injury in pediatric patients from GC incidents and compare them with those of ATVs, a review of trauma databases from multiple trauma centers in a single state was performed. Our hypothesis was that both GC and ATV injuries would show an increase over time and that the severity of GC injuries is on par with those injuries sustained in ATV traumas.…”
Section: Introductionmentioning
confidence: 99%
“…Ejection and rollover were the most common mechanisms of injury, and the most common position for an injured golf cart occupant was a passenger (52.2%). A study of 108 golf cart-injured patients up to the age of 17 years revealed that the majority of the patients (75.9%) sustained at least one bone fracture (89). The majority of injuries occurred in children (50.8%) who seem to be more vulnerable to golf cart-related injuries than adults (90,91).…”
Section: Resultsmentioning
confidence: 99%